UPGRADING OF MOROCCAN OLIVE MILL WASTEWATER USING ELECTROCOAGULATION: KINETIC STUDY AND PROCESS PERFORMANCE EVALUATION - Reda Elkacmi; Noureddine Kamil; Mounir Bennajah (Journal of Urban and Environmental Engineering, 2017)
Treatment of olive mill wastewater (OMW) by electrocoagulation (EC) was investigated in a stirred tank reactor (STR), the effect of dif ferent influential parameters , namely, contact time, current density and pH was determined. O ver 72 % of COD, 93 % of polyphenols and 95 % of color intensity were re moved efficiently at pH of 5.2, current density of 58.33 mA/cm 2 and a residence time of 45 min. A kinetic study of these three parameters was carried out and both COD an d dark color removal obey the first-order law model. On the other hand, the polyphen ols reduction, fits the pseudo second-order model with cu rrent- dependent parameters. A variable order kinetic (VOK) model derived fro m the Langmuir-Freundlish equati on was proposed to determine the kinetics of pollutant removal reactions with EC. Results showed that the model equations strongly fit the experimental concentrations of the three pollutants.